ANALYSIS OF IMPROVING THE PERFORMANCE OF EMPLOYEES OF THE PADANG HEALTH CENTER OF LUMAJANG REGENCY WITH VARIABLES OF WORK MOTIVATION, WORK DISCIPLINE AND WORK ENVIRONMENT - Putri, Revi Ayu Permana; Winahyu, Pawestri; Tyas, Wenny Murtalining (Universitas Muhammadiyah Tangerang, 2024)
Technological advances that are increasingly stringent employees are expected to make their best contribution to the agency. Employees who have good performance are human resources needed by an organization and company to achieve company goals. In this study, the researcher had the opportunity to carry out research at the Padang Health Center, Lumajang Regency. This study aims to analyze the improvement of the performance of employees of the Padang Health Center in Lumajang Regency with variables of work motivation, work discipline and work environment. This research was conducted using a quantitative approach method. Sampling was carried out by census (saturated), the number of samples in this study was 63 respondents. The data collection techniques in this study are questionnaires and library data. The analysis used in this study is Multiple Linear Analysis with the help of SPSS software version 25. The variable of work motivation can be concluded that work motivation affects the performance of Puskesmas employees, then it can be concluded that work discipline affects the performance of Puskesmas employees by 28.2%. The work environment variable has a significance of the T test value of 0.025 < 0.05, so it can be concluded that the work environment affects employee performance partially with an influence of 11.5%. The conclusion of this study is that work motivation, work discipline and work environment have a positive and significant effect on the performance of employees of the Padang Health Center of Lumajang Regency.